Social support from friends predicts changes in memory specificity following a stressful life event. Issue 9 (21st October 2019) - Chiu, Christine H. M.; Ma, Hon Wing; Boddez, Yannick; Raes, Filip; Barry, Tom J.
ABSTRACT: Exposure to negative life stress has been associated with difficulty retrieving memories for specific autobiographical events, with important consequences for the emergence of emotional disorders. We examined whether social support can protect against the effects of negative events on memory specificity. University students ( N = 143) were assigned to groups based on whether or not they experienced a negative stressor, operationalised as whether or not their recent exam performance was in line with their expectations. After receiving their exam results (T1), and one month later (T2), participants completed measures of memory specificity, their attitudes towards themselves and the occurrence of other stress-related events. Participants also completed a general measure of perceived social support from friends, family, and significant others, and an equivalent measure for social support related to performance. For participants who experienced an exam-related stressor, reduced performance-specific social support from friends was associated with reduced memory specificity at T2, even when accounting for T1 memory specificity, individual differences in attitudes towards self, the experience of additional stressors, and gender. No such relation was present for participants who did not experience a stressor. These findings provide new understanding of the influence of social variables on autobiographical memory specificity.